Propagation characteristics of surface waves on half-space of piezoelectric semiconductor with rotation effect considered - Li Li; Tong Wu; Qian Zhang (Results in Physics)
In this paper, the propagation characteristics of generalized surface waves on a piezoelectric semiconductor half-space with the presence of the rotation are studied. First, the governing equations of motion of the piezoelectric semiconductor solid which rotates about any axis are derived by the method of vector decomposition. Next, the dispersive relations of generalized Rayleigh wave and generalized Shear surface wave are obtained. The dispersion, attenuation and frequency shift features of generalized Rayleigh wave and generalized Shear surface wave under two different boundary conditions are studied numerically with considering the rotation and the biasing electric fields. Influences of the rotation round axes with different azimuthal angles on the dispersion, attenuation and frequency shift of surface waves are discussed for both cases of open circuit and short circuit.